Electrochemical fingerprint of street samples for fast on-site screening of cocaine in seized drug powders. Issue 3 (15th January 2016) - de Jong, Mats; Sleegers, Nick; Kim, Jayoung; Van Durme, Filip; Samyn, Nele; Wang, Joseph; De Wael, Karolien
Abstract : Application of a novel electrochemical fingerprint strategy leads to improved screening, allowing simultaneous detection of cocaine and cutting agents. Abstract : We report on a wearable fingertip sensor for on-the-spot identification of cocaine and its cutting agents in street samples. Traditionally, on-site screening is performed by means of colour tests which are difficult to interpret and lack selectivity. By presenting the distinct voltammetric response of cocaine, cutting agents, binary mixtures of cocaine and street samples in solution and powder street samples, we were able to elucidate the electrochemical fingerprint of all these compounds. The new electrochemical concept holds considerable promise as an on-site screening method.